Fiscal discipline as a social norm: the European Stability Pact - Fitoussi, Jean-Paul; Saraceno, Francesco (Paris, 2007)
"This paper reviews the arguments for and against the 'Stability and Growth Pact' signed by the countries of the Euro area. We find the theoretical debate to be inconclusive, as both externality and credibility arguments can be used to yield opposite, and equally plausible conclusions. We also argue that evidence in favour of a Pact-like rule is scant. We therefore suggest the view that the Stability Pact is a public social norm, and that a country's adherence to that norm is in fact a response to the need to preserve reputation among the other members of the European Union. Using this extreme but not implausible hypothesis, we build a simple model similar in spirit to Akerlof's (1980) seminal paper on social norms, and we show that reputation issues may cause the emergence of a stable but inferior equilibrium. We further show that after the enlargement, with a number of countries anxious to prove their 'soundness' joining the club, the problems posed by the pact/social norm are likely to increase."